2020
DOI: 10.1108/jmd-05-2019-0211
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive organizations: developmental reciprocity through authentic leader-employee relationships

Abstract: PurposeBuilding on previous research that focused on Walgreens inclusive managers in South Carolina and Georgia, we studied leadership practices in Connecticut where effective and inclusive teams are developed.Design/methodology/approachUsing the case study approach, interviews with over 90% of the managers in a Walgreens distribution center where over a third of its workforce of 500 employees has a disability were conducted.FindingsCreating an inclusive workplace dramatically altered the culture of the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…Additionally, employees will take the initiative to maintain good rapport with others when they expect to be rewarded (Cortez and Johnston, 2020). Simultaneously, the reciprocity principle states that when employees perceive benefits from supervisors, they will work harder to reward their boss (Moore et al, 2020). The work-related resources provided by the organization will affect employees' psychological perceptions.…”
Section: Supervisor Helping Behavior and Employee Voice Behaviormentioning
confidence: 99%
“…Additionally, employees will take the initiative to maintain good rapport with others when they expect to be rewarded (Cortez and Johnston, 2020). Simultaneously, the reciprocity principle states that when employees perceive benefits from supervisors, they will work harder to reward their boss (Moore et al, 2020). The work-related resources provided by the organization will affect employees' psychological perceptions.…”
Section: Supervisor Helping Behavior and Employee Voice Behaviormentioning
confidence: 99%
“…Menurut Khaola dan Rambe (2020), apabila komitmen organisasi wujud, maka kepimpinan kebaktian berupaya meningkatkan kecenderungan kakitangan untuk mempamerkan OCB dan seterusnya memberi kesan yang terhadap keberkesanan organisasi. Menurut Moore et al (2020), perkhidmatan pemimpin kepada kakitangan akan menghasilkan perkhidmatan timbal balik daripada kakitangan kepada pemimpin. Jika pemimpin melayani kakitangan, maka kakitangan akan meneladaninya dengan memberi perkhidmatan kepada orang lain (Greenleaf 1977).…”
Section: Komitmen Organisasi Sebagai Pengantara Dalam Hubungan Antara...unclassified
“…Keadaan ini amat bersesuaian dengan konsep organisasi bukan berasaskan keuntungan yang memberi perkhidmatan kepada masyarakat. Pendekatan yang sama turut diperjelaskan oleh Moore et al (2020), iaitu kakitangan yang…”
Section: Komitmen Organisasi Sebagai Pengantara Dalam Hubungan Antara...unclassified
“…Neuroticism is a boundary condition in the mediation effect of relatedness need satisfaction in the said association [87]. Similarly, scientists revealed that leaders with greater mindfulness build authentic leadership behaviors with their subordinates, and gain greater adaptability, innovation, resiliency, and improved engagement [88]. Thus, evaluating the trait mindfulness of job applicants for leadership positions is suggested [89].…”
Section: Mindfulness On Leadership and Relationshipsmentioning
confidence: 99%